(untitled) (Journal of Oriental Studies, 2018)
This article is devoted to a very popular problem of our time. In the article as one of the directions of the soft power of modern Japan anime and manga are examined. A special place is given to the main provisions of Joseph Nye’s soft rower concept, the policy of Cool Japan. Shown a brief history of the birth of anime and manga since the 12th century. The role of anime and manga as an instrument of the external cultural policy of modern Japan, distribution geography, successes and causes of failures has been analyzed.